2003
DOI: 10.1021/bi034678d
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis Study on the Zebra Fish SOX9 High-Mobility Group:  Comparison of Sequence and Non-Sequence Specific HMG Domains

Abstract: A unique class of proteins, containing high-mobility group (HMG) domain(s), recognizes unusual DNA structures and/or bends specific to AT-rich linear double-stranded DNA. The DNA binding feature of these proteins is exhibited in the HMG domain(s). Although the sequence specific and non-sequence specific HMG domains exhibit very high degrees of sequence similarity, the reasons for the difference between their DNA recognition mechanisms are unclear. A series of zebra fish SOX9 HMG domain mutants was prepared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…Some highly conserved residues have been identified as very important in sequence specificity of HMG domains, but these residues alone are not the sole determinant of sequence specificity [reviewed in (47)]. Rather, sequence-specificity appears to be a combination of effects of residues on the domain's positioning, affinity, its stability in complex with DNA, the number of interactions on the protein–DNA interface and the number of base-specific contacts (49). Studies of the HMG domain indicate the difference between sequence-specific and sequence-non-specific members of the same family is generally more complex than the simple substitution of contact residues for neutral residues.…”
Section: Discussionmentioning
confidence: 99%
“…Some highly conserved residues have been identified as very important in sequence specificity of HMG domains, but these residues alone are not the sole determinant of sequence specificity [reviewed in (47)]. Rather, sequence-specificity appears to be a combination of effects of residues on the domain's positioning, affinity, its stability in complex with DNA, the number of interactions on the protein–DNA interface and the number of base-specific contacts (49). Studies of the HMG domain indicate the difference between sequence-specific and sequence-non-specific members of the same family is generally more complex than the simple substitution of contact residues for neutral residues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent alanine scanning mutagenesis study performed on the Sox-9 HMG domain from zebra fish revealed the importance of certain residues and their influence on protein stability and DNA binding (63). In addition, the authors calculated a theoretical "instability index" and reported the average instability indices to have contrasting values of 67 and 30 for the sequence-specific and non-sequencespecific subclasses, respectively (the higher the value, the greater the instability).…”
Section: Structural Differences Between Free and Bound Statesmentioning
confidence: 99%
“…The HPLC-purified glycine extended wild-type Sco-CHH (Sco-CHH-Gly), and glycine extended and alanine-substituted Sco-CHHs (I2A, F3A, D4A, D12A, R13A, Q51A, E54A, D60A, I69A, and V72A Sco-CHH-Gly) were individually dissolved in 10 mM PBS (150 mM NaCl, pH 6.8) at 20–30 μM; an aliquot (200 μl) of the samples was placed in a 1-mm cell and data collected from 260 nm to 200 nm in 0.5 nm increments at 25°C. Raw data were baseline corrected, smoothed, and transformed to obtain spectra in units of mean residue ellipticity and the ellipticity at 222 nm was used to estimate the α-helical content of the peptides [ 40 ].…”
Section: Methodsmentioning
confidence: 99%